Sonata Op. 36 para violino e piano de Henrique Oswald: aspectos técnicos e interpretativos - Marija Mihajlovic Pereira (2015)
This paper explores the technical and interpretative aspects of the Sonata Op. 36 for violin and piano by Henrique Oswald. With consideration of the composer's trajectory between Italy and Brazil, the European influences in the sonata are outlined through formal analysis as well as comparison with other works of the Romantic period. Considering these influences, bowings, bowstrokes, fingerings, dynamics, and agogic accents are suggested. In addition, the work includes observations as to appropriate bow placement and bow use, the use of vibrato, articulation, balance between the violin and piano, musical texture and musical character: all with a view to presenting a well founded interpretation from an aesthetic and stylistic point of view. The final result of this research is a performance edition of the violin part, including the suggestions listed above.